Regioselectivity Patterns in Radical Cyclization of Diosphenol Derivatives with Different Ring Size: A Combined Experimental and DFT Study - Boz, Esra; Ozcan, Hafize; Zaim, Omer; Tuzun, Nurcan S.; Tüzün, Nurcan (Wiley, 2021)
Abstract Radical cyclization reactions are still a challenging field in synthetic organic chemistry. Herein, the radical reactions of 6‐ and 7‐membered diosphenol derivatives (tropolone) with a significant difference in reactivity, ring size, aromaticity and stability were investigated. While the former produces a mixture of products including oxabicycloalkanones, the experimental work performed herein resulted with a single 2‐(3‐hydroxypropyl)cyclohepta‐2,4,6‐trienone product, regioselectively. DFT calculations (UM05/6‐311++G(d,p)) were performed following the experimental studies in order to describe the outcomes correctly. Therefore, all possible reaction pathways were investigated for both diosphenol and tropolone. The reaction barriers and intrinsic barriers from the Marcus theory were calculated to investigate the thermodynamic and intrinsic electronic effects to the experimental product distribution. Both experiment and theory show that the aforementioned systems have different selectivity routes governed by several factors. As a result of this comparative study, the charge distribution at the reactive atoms, entropy factors for cyclization vs termination and aromatization of the ring effects were found to be the driving factors for the observed regioselectivity.
Keywords: Fragmentations; Closure; Competition; Diallylamine; Monomers; Stereoselectivity; DFT; Tropolone; Radical Cyclization; Regioselectivity; Marcus Theory; Diosphenol; Oxidation; Endo-Exo Selectivity; Path; Mechanism; Cyclopolymerization